ANALISIS FAKTOR YANG MEMPENGARUHI PASOKAN MINYAK GORENG BEKAS RUMAH MAKAN MENGGUNAKAN ISM (interpretive structure modelling) DANMICMAC (cross-impact matrix multiplication applied to the classification) - SUTARMAN GAFUR, TH. CANDRA WASIS AGUNG S, NOVIRA KUSRINI, (Jurnal Social Economic of Agriculture, 2018)
Waste cooking oil(jelantah) can be founded in eatery as one of food process services businees with a varies supply number. The varies jelantah supply number conditions need to analyze with Interpretive structure modeling and Cross-Impact Matrix Multiplication Applied to The Classification(MICMAC).The objective of the study were: 1) to analyzed the factors that affected the jelantah supply number and2) to find the succesfully key factors of the jelantah supply number. Nine indicators used in survey at 61 eateries, consulting with expert and as data analysis. The result can be shown: 1) founded 4 level with the performance of jelantah producer and partnerships commitment as a main controlled factors of the jelantah supply number 2). Founded the 5 element succesfully key factors in the jelantah supply number of eateriesthat it consists the collection system, the number of collectors, the number and the type of producers, the amount of cooking oil consumption and the price of jelantah.Keywords : eateries, jelantah,key factor,methode